Tailoring superstructure units for improved oxygen redox activity in Li-rich layered oxide battery’s positive electrodes - Hao Liu; Weibo Hua; Sylvia Kunz; Matteo Bianchini; Hang Li; Jiali Peng; Jing Lin; Oleksandr Dolotko; Thomas Bergfeldt; Kai Wang; Christian Kübel; Peter Nagel; et al. (Nature Communications)
Abstract The high-voltage oxygen redox activity of Li-rich layered oxides enables additional capacity beyond conventional transition metal (TM) redox contributions and drives the development of positive electrode active materials in secondary Li-based batteries. However, Li-rich layered oxides often face voltage decay during battery operation. In particular, although Li-rich positive electrode active materials with a high nickel content demonstrate improved voltage stability, they suffer from poor discharge capacity. Here, via physicochemical and electrochemical measurements, we investigate the correlation between oxygen redox activity and superstructure units in Li-rich layered oxides, specifically the fractions of LiMn6 and Ni4+-stabilized LiNiMn5 within the TM layer. We prove that an excess of LiNiMn5 hinders the extraction/insertion of lithium ions during Li metal coin cell charging/discharging, resulting in incomplete oxygen redox activity at a cell potential of about 3.3 V. We also demonstrate that lithium content adjustment could be a beneficial approach to tailor the superstructure units. Indeed, we report an improved oxygen redox reversibility for an optimized Li-rich layered oxide with fewer LiNiMn5 units.